2013
DOI: 10.1055/s-0033-1361926
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Uterine Rupture during Second Trimester Leading to Successful Pregnancy Outcome: Case Study and Literature's Review

Abstract: It was thought to be impossible to prolong the pregnancy in a case of uterine rupture in the second trimester. We encountered a case of rupture of the pregnant uterus in early mid-trimester, which we repaired with suture and overlapping of collagen fleece coated with fibrin glue, resulting in pregnancy prolongation until the 34th week. Our case and five previously reported cases were reviewed. Pregnant uterine rupture in mid-trimester could be repaired with suture and overlapping of collagen fleece in the abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
0
11
0
8
Order By: Relevance
“…Shiratani et al reported that they repaired the area with fleece-coated fibrin glue in combination with closing the ruptured area by absorbable suture of a case who was admitted with hemoperitoneum in week 24 of the gestation, thus the pregnancy is prolonged until 35 weeks. 8 Sugawara et al presented 5 cases as well as their case. All cases are within second trimester.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Shiratani et al reported that they repaired the area with fleece-coated fibrin glue in combination with closing the ruptured area by absorbable suture of a case who was admitted with hemoperitoneum in week 24 of the gestation, thus the pregnancy is prolonged until 35 weeks. 8 Sugawara et al presented 5 cases as well as their case. All cases are within second trimester.…”
Section: Discussionmentioning
confidence: 96%
“…8 An other case was restored with double layer sutured monocryl, single layer sutured with 3-0 Vicryl. The case reported by Roeters et al was restored with a single layer chromic catgut with successful continuation of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…A RU no segundo trimestre pode ser reparada com sutura e sobreposição de lã de colágeno, se a placenta percreta está ausente. Quando a placenta percreta é suspeitada, monitorização ultrassonográfica precisa ou laparotomia diagnóstica pode ser necessária após o reparo 35 . Em casos de RU em que a paciente esteja hemodinamicamente estável, é possível uma abordagem totalmente laparoscópica 59 .…”
Section: Discussionunclassified
“…До недавнего времени единственно возможным алго-ритмом действия при разрыве матки во втором триместре беременности, сопровождающимся внутренним крово-течением, считалось немедленное выполнение оператив-ного вмешательства -кесарево сечение с последующей гистерэктомией [7,13]. Однако некоторые специалисты на примере собственных случаев продемонстрировали, что консервативное лечение спонтанного разрыва матки во втором триместре беременности до достижения зрелости плода можно рассматривать в качестве альтернативы ги-стерэктомии [4,10].…”
unclassified
“…Sugawara et al (2014), сообщил об успешном слу-чае пролонгирования беременности до срока 34 недель, после хирургического восстановления разрыва матки, случившегося во втором триместре беременности. Авто-ры сообщили, что на данный момент зарегистрировано всего пять случаев успешного восстановления разрыва матки во втором триместре при отсутствии врастания плаценты [13].…”
unclassified